SUMOylation regulates cytochrome P450 2E1 expression and activity in alcoholic liver disease. Issue 6 (18th January 2018) - Tomasi, Maria Lauda; Ramani, Komal; Ryoo, Minjung; Cossu, Carla; Floris, Andrea; Murray, Ben J.; Iglesias-Ara, Ainhoa; Spissu, Ylenia; Mavila, Nirmala
ABSTRACT: Alcohol acts through numerous pathways leading to alcoholic liver disease (ALD). Cytochrome P450 (CYP2E1), an ethanol‐inducible enzyme, metabolizes ethanol‐producing toxic reactive oxygen species (ROS) and is regulated at the posttranslational level. Small ubiquitin‐like modifier (SUMO)ylation is a posttranslational modification that involves the addition of SUMOs, which modulate protein stability, activity, and localization. We demonstrated that ubiquitin‐conjugation enzyme 9, the SUMO‐conjugating enzyme, is induced in the livers of an intragastric ethanol mouse model. Our aim is to examine whether SUMOylation could regulate ethanol‐induced CYP2E1 expression in ALD and to elucidate the molecular mechanism(s). CYP2E1 and UBC9 expression in vitro and in vivo was detected by real‐time PCR and immunoblotting/immunostaining. SUMOylation was assayed by mass spectrometry and coimmunoprecipitation. Ubc9 expression was induced in ethanol‐fed mouse livers, and silencing inhibited ethanol‐mediated CYP2E1 microsomal retention and enzymatic activity. CYP2E1 SUMOylation was found to be induced by ethanol in vitro and in vivo. Ubc9 silencing prevents ethanol‐induced lipid accumulation and ROS production. UBC9 was highly expressed in human ALD livers. Finally, we found that lysine 410 is a key SUMOylated residue contributing to CYP2E1 protein stability and activity preventing CYP2E1 SUMOylation. Ethanol‐mediated up‐regulation of CYP2E1 via SUMOylation enhancing its protein stability and activity and may have important implications in ALD.—Tomasi M. L., Ramani, K., Ryoo, M., Cossu, C., Floris, A., Murray, B. J., Iglesias‐Ara, A., Spissu, Y., Mavila N. SUMOylation regulates cytochrome P450 2E1 expression and activity in alcoholic liver disease. FASEB J. 32, 3278–3288 (2018). www.fasebj.org